Analysis of the association of parameters in the formation of ultrafine fibers from PEI and PMMA - Kukulka, Elisa Camargo; Souza, Joyce Rodrigues de; Santos, Jessica Dias; Campos, Tiago Moreira Bastos; Borges, Alexandre Luiz Souto (Brazilian Dental Science, 2021)
Objective: The aim of the study was to fabricate and morphologically characterize ultrafine Polyetherimide fibers (PEI) associated with Polymethylmethacrylate (PMMA) – PP (group formed by the association of PEI with PMMA), produced by the electrospinning process. Material and Methods: A solution of PEI (0.562 g) + PMMA (0.377 g) dissolved in 2.5 mL of chloroform, 0.85 mL of Dimethylformamide (DMF) and 0.85 mL of 1.1.2.2 Tetrachloroethane (TCE) was prepared. For the electrospinning process, different continuous voltages (10 to 18 kV) and two different distances (8 and 12 cm) between the needle tip and the collecting apparatus were used, giving rise to 6 distinct groups of ultrafine fibers (PP 1 to 6) that were observed in Scanning Electron Microscopy to check for defects and calculate the average diameter of the fibers. Results: The best parameter, the parameter that was most effective for the production of fibers, observed was subjected to Energy Dispersion X-ray Spectroscopy (EDS), X-ray Diffraction (XRD) and Contact Angle Analysis tests. The data were analyzed using the ANOVA and Tukey test (p